Compsodactylus Fuhrmann, 2012 (Coleoptera: Scarabaeidae: Melolonthinae): distributional notes and a new species - Fuhrmann, Juares; Smith, Andrew B.t. (Zootaxa, 2021)
A new species of Compsodactylus Fuhrmann, 2012 (Coleoptera: Scarabaeidae: Melolonthinae: Macrodactylini) is described from Peru. New provincial records for Compsodactylus argentinus (Moser, 1919) are detailed for Argentina: Córdoba and Misiones. A revised key to Compsodactylus species is presented.